An analysis of the national strategies for sustainable development with special emphasis on the issues of Agriculture and Rural development - Bauerné Gáthy, Andrea (Applied Studies in Agribusiness and Commerce, 2008)
In this paper which is based on my dissertation I carried out a comprehensive analysis of the national strategies for sustainable development prepared by the EU and its member states. I paid special attention to agricultural and rural development issues discussed in the strategies. According to my hypothesis the sets of objectives defined in accordance with the principles of sustainable development provide a firm basis for the objectives of the ongoing reforms of the European Union’s CommonAgricultural Policy. Due to the complexity of the topic I applied an interdisciplinary approach in my research.